Short-term persistence in hybrid mutual fund performance: The role of style-shifting abilities - Herrmann, Ulf; Scholz, Hendrik (Journal of Banking & Finance, 2013)
Our study analyzes the performance of hybrid mutual funds. Based on two extended Carhart models we determine total fund performance by comparing fund returns to investable fund-specific style benchmarks. Using daily returns and a quarterly measurement interval, we present an innovative return-based approach to decompose total performance into in-quarter abnormal performance and style-shifting performance. In addition, we split total style-shifting performance into active and passive components. In this context, we confirm possible benefits of these performance measures by analyzing several simulated investment strategies. Our empirical study covers 520 hybrid mutual funds from 10/1998 to 12/2009 and shows that hybrid mutual funds (i) do not outperform their benchmarks on average, (ii) partially show positive in-quarter abnormal performance and style-shifting abilities, and (iii) exhibit short-term persistence in in-quarter abnormal performance but not in style-shifting abilities.